Research on the Mechanical Properties and Weldability of Wh630e Plate with VN Micro-Alloying. (2015) - Wang, X.J.; Li, S.R.; Liu, W.B.; Hu, Y.H.; Liu, W.Y.; Zhan, G.F.; Hong, X.; Yang, X.L.
Abstract: Stable VN micro-alloying for WH630E steel plate can be achieved by utilization of blowing nitrogen at the bottom of BOF and refining process. Steel plate WH630E with thickness of 8-25 mm was rolled by TMCP process and was treated by normalizing. By comparing mechanical properties and microstructure changes in as-rolled plate and normalized plates, it was found out that ferrite grain size can be refined by normalizing process and the low temperature impact energy can be improved by normalizing. The main Strengthening mechanism for normalized WH630E steel plate was ferrite grain refining, grain refining plays a more stronger role than V(CN) precipitation strengthening. Cold crack and reheated crack can be avoided by preheating treatment with no more than 170 ̊C before welding WH630E plate, strength and toughness for welded joint can have good match with the base metal by the process of 15∼35 kJ/cm welding heat input energy and 500∼580 ̊C SR(stress relief)heat treatment. Yield strength of normalized high strength pressure vessel steel plate can be improved by VN micro-alloying, and then the wall thickness of pressure vessel can be thinned or operating pressure can be increased, therefore overall weight of transportable pressure vessel can be reduced, and there will be significant economic and social benefits for the application of this kind pressure vessel steel plate.